Table tennis tactics your path to success - Geske, Klaus-M; Mueller, Jens (Meyer & Meyer Sport, 2010)
This book shows you the most important table tennis tactics. The book contains an age-appropriate collection of all aspects of table tennis tactics for young players. It helps you to read your opponent's game and to decide how to play against forehand or backhand-dominant players. There are also valuable tips on how playing tempo can be used as a tactical element, how to produce and read ball spin and how to influence it with a suitable racket surface, and how the service game is used to take tactical control of the game. With numerous photos and illustrations, a self-test questionnaire, portraits of the best table tennis players, the official rules and tactical know-how, this book will soon become your table tennis 'bible'.